ANALISA KONDISI FISIK SUMUR GALI DI DUSUN II DESA SEI TUAN KECAMATAN PANTAI LABU KABUPATEN DELI SERDANG TAHUN 2019 - Seri Asnawati Munthe; Yenni Tarigan; Linta Antasari Bali (Yayasan Akrab Pekanbaru, 2019)
This study aims to determine the physical condition of dug well water in Hamlet II Sei Tuan Village Labu Subdistrict Deli Serdang Regency in 2019. This type of research is a survey research with cross sectional descriptive design. Sampling was done by purposive sampling method, overall samples taken were 31 samples. Data collection is done by means of observation, interviews and measurements. Analysis of the data used is univariate analysis and then analyzed descriptively. The results of the septic tank distance that did not meet the requirements were 26 (83.9%), and the physical condition of dug wells that was not appropriate, namely the waste water drainage (SPAL) that was broken / absent with a percentage of 51.6% and the condition of the well covering the lips wells that meet the requirements of 29%, wells floors meet the requirements of 29%, wells that meet the requirements of 74.2% and non-cracked floors 45.2%. It is expected that the government will participate in carrying out monitoring and supervision efforts on dug well water which utilized by the people of Sei Tuan Village, the community that uses dug wells is expected to make improvements to the dug well facilities and pay more attention to the source of pollutants.